Sistem Pendidikan di Negara Jerman - Siti Junaimah; Agus Faisal Asyha (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the education system in Germany from historical, philosophical, sociological, geographical, juridical, and psychological perspectives, as well as to examine the educational system, curriculum, and the roles of government and society in supporting national education. This study is important because Germany is recognized as one of the countries with a high-quality education system and serves as a reference in comparative education studies worldwide. Through this research, a comprehensive understanding of the characteristics, strengths, and implementation of the German education system is expected to be achieved. This research employs a qualitative approach using a library research method. Data were collected from various academic sources, including books, journal articles, educational policy documents, reports from international organizations, and other scholarly publications related to the German education system. The collected data were analyzed using content analysis techniques through the processes of data collection, reduction, presentation, and conclusion drawing to provide a systematic and in-depth description of Germany’s education system. The findings indicate that the German education system is built upon the principles of equal educational opportunities, competency development, and strong integration between education and labor market needs. The system includes formal, non-formal, and informal education, covering preschool, primary, secondary, and higher education levels. The strengths of the German education system are reflected in the implementation of the Dual Vocational Education System, competency-based curricula, highly professional teachers, and strong support from both the government and society. Therefore, the German education system can serve as a valuable reference for improving the quality and effectiveness